2004
DOI: 10.5715/jnlp.11.5_63
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Paraphraser and Transfer for Spoken Language Translation

Abstract: One of the problems in spoken language translation is the enormous variety of expressions not found in text translation.This volume can lead to a sparse translation coverage.In order to tackle this problem,we propose a machine translation model where an input is translated through both source-language and target-language paraphrasing processes.In this paper,we discuss the source paraphrasing and the language transfer processes,and the design of our translation model.In the source language paraphrasing,we take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Paraphrases generated from the resource as additional examples Previous research has shown that the introduction of paraphrases may improve the quality of machine translation output: paraphrases may be added in the source language (Yamamoto, 2004) or in the target language (Habash, 2002).…”
Section: Dictionaries As Lists Of Particular Examplesmentioning
confidence: 99%
“…Paraphrases generated from the resource as additional examples Previous research has shown that the introduction of paraphrases may improve the quality of machine translation output: paraphrases may be added in the source language (Yamamoto, 2004) or in the target language (Habash, 2002).…”
Section: Dictionaries As Lists Of Particular Examplesmentioning
confidence: 99%